The negotiation and implementation of Treaty 7, through 1880 - Robert, Sheila; University of Lethbridge. Faculty of Arts and Science (Lethbridge, Alta. : University of Lethbridge, Faculty of Arts and Science, 2007, 2007)
375 leaves 29 cm. The objective of this thesis is to examine the archival documents that may be considered by the Supreme Court of Canada if the Treaty 7 Nations were to challenge the Federal Government on the Treaty’s content and meaning. The impetus for this thesis is two-fold. Firstly, recent decisions by the Supreme Court of Canada, in relation to Aboriginal historical treaties, have demonstrated a shift towards legally recognizing the sovereignty of First Nations. As more First Nations challenge the Federal Government on their fulfillment of treaty obligations, Supreme Court decisions will become more elaborate and exhaustive, providing many Nations with an opportunity to address treaty concerns in a more substantive manner than in the past. Secondly, the Blackfoot are my neighbours and I am very honoured to relay part of their story.